Inhibitive effects of isatin, thiosemicarbazide and isatin-3-(3-thiosemicarbazone) on the corrosion of aluminium alloys in nitric acid - Singh D.D.N.; Singh M.M.; Chaudhary R.S.; Agarwal C.V. (My University, 2025)
The inhibitive efficiencies of isatin, thiosemicarbazide and their condensation product, i.e. isatin-3-(3-thiosemicarbazone) are studied at different concentrations in relation to corrosion of aluminium alloys (1060,1100, 3003) in 20% nitric acid at 30, 40 and 50° C using the weight loss method. Polarization experiments have been performed at 0.05, 0.2 and 0.3% concentrations of the inhibitors at 30° C. It is found that isatin-3-(3-thiosemicarbazone) is a more effective inhibitor as compared to the parent compounds for the three alloys at all the experimental temperatures. The effectiveness of the inhibitors increases with increase in temperature from 30° C to 50° C. The inhibitors are found to retard the corrosion by predominantly acting on local cathodes although they are also partially effective on the anodes. The critical current density for the passivation of aluminium decreases almost in the same order as the inhibition efficiency of the inhibitors increases. © 1980 Chapman and Hall Ltd.